USING OF FIBROUS WASTE FROM COMPREHENSIVE PROCESSING OF ALGAE BIOMASS OF THE GENUS ZOSTERA AS A RAW MATERIAL FOR THE PRODUCTION OF PAPER MATE-RIALS - Karaiumer, Anastasiia; Kustovska, Antonina (Science-based technologies, 2025)
The study demonstrates the potential of using the biomass of seagrasses from the Zosteraceae family (particularly Zostera marina) from storm deposits as an alternative to traditional raw materials for paper production. Research samples were collected during different seasons along the coasts of the Black Sea (Ukraine) and the Mediterranean Sea (Turkey), which enabled a comparative analysis of the influence of regional and seasonal factors on the properties of the raw material. It was established that the yields of lipids, pectic substances, and cellulose-containing residue vary significantly depending on the location and season of biomass collection. Experimental paper samples were produced from the solid cellulose-containing residue without the addition of binding components. The best strength and density characteristics were observed in paper samples made from biomass collected during the spring-summer period, when the cellulose content in the plants reaches its peak. Paper produced from Ukrainian raw material demonstrated higher tensile strength compared to samples made from Turkish biomass, which is attributed to differences in the ecological growth conditions of the plants. Microscopic analysis confirmed the presence of long fibers in the paper structure, which positively affects its physical and mechanical properties. The developed technological scheme for the comprehensive processing of Zostera marina biomass allows for the efficient transformation of storm-deposited seagrass into valuable raw material for the paper industry. The application of this technology has a significant environmental impact, contributing to the cleaning of coastal ecosystems, reducing deforestation, and promoting the development of the circular economy. The results obtained confirm the feasibility of producing satisfactory-quality paper materials from Zostera biomass, which could become an important step toward diversifying the raw material base of the pulp and paper industry. Further research will focus on optimizing processing parameters and improving the quality characteristics of paper products made from seagrass.